Organic light-emitting device and display device comprising same
By using specific substituted phenanthroline compounds as charge generation layer material in organic electroluminescent devices, combining with electron transport layer to optimize device structure, the problem of insufficient luminescence efficiency and life in the prior art is solved, and high efficiency and Long-life organic electroluminescent devices.
Patent Information
- Application Number
- CN202310731075.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
AI Technical Summary
The luminous efficiency and service life of existing organic electroluminescent devices are insufficient, and it is difficult to effectively improve through the optimization of structure and materials.
A specific replacement phenanthroline compound is used as the charge generation layer material, combined with the electron transport layer, and the device structure is optimized to improve charge transport performance and luminous efficiency and extend service life.
The luminescence efficiency of organic electroluminescent devices is significantly improved, the driving voltage is reduced, and its service life is extended.
Smart Images

Figure CN119173069A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic light-emitting display, and in particular to an organic electroluminescent device and a display device comprising the same. Background Art
[0002] Electroluminescence (EL) refers to the phenomenon that luminescent materials emit light under the action of electric field, stimulated by current and voltage. It is a luminescence process that directly converts electrical energy into light energy. Organic electroluminescent displays (hereinafter referred to as OLEDs) have a series of advantages such as autonomous luminescence, low-voltage DC drive, full curing, wide viewing angle, light weight, simple composition and process. Compared with liquid crystal displays, organic electroluminescent displays do not require backlight sources, have large viewing angles, low power consumption, and their response speed can reach 1000 times that of liquid crystal displays, but their manufacturing cost is lower than that of liquid crystal displays with the same resolution. Therefore, organic electroluminescent devices have a very broad application prospect.
[0003] With the continuous advancement of OLED technology in the two major fields of lighting and display, people are paying more attention to the research on high-efficiency organic materials that affect the performance of OLED devices. An organic electroluminescent device with high efficiency and long life is usually the result of the optimized combination of device structure and various organic materials. This has brought great opportunities and challenges to chemists in designing and developing functional materials of various structures. Laminated devices can effectively improve the working life of devices, so they have been a research hotspot in recent years. How to develop high-efficiency charge generation layer materials and select matching light-emitting units to improve the luminous efficiency of organic electroluminescent devices and extend their service life has become a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0004] The object of the present invention is to provide an organic electroluminescent device and a display device comprising the same, so as to improve the luminous efficiency of the organic electroluminescent device and prolong its service life.
[0005] The first aspect of the present invention provides an organic electroluminescent device, the organic electroluminescent device comprising a charge generation layer and an electron transport layer, the charge generation layer material comprising a compound of formula (I):
[0006]
[0007] in,
[0008] R 1 ,R 2 is selected from hydrogen, unsubstituted or Rc-substituted C 6 -C 30 Aryl, unsubstituted or Rc-substituted C 3 -C30 heteroaryl;
[0009] Ar 1 Selected from C containing N atom which is unsubstituted or substituted by Rc 3 -C 30 heteroarylene;
[0010] L 1 , L 2 Selected from chemical bonds, unsubstituted or Rc-substituted C 6 -C 30 Arylene, unsubstituted or Rc-substituted C 5 -C 30 heteroaryl;
[0011] The heteroatoms on the heteroaryl or heteroarylene group are each independently selected from O, S or N;
[0012] The substituents Rc of each group are independently selected from hydrogen, deuterium, halogen, nitro, cyano, C 1 -C 4 Alkyl, phenyl, biphenyl, terphenyl, pyridyl, pyrimidinyl or naphthyl.
[0013] A second aspect of the present invention provides a display device, which comprises the organic electroluminescent device provided by the first aspect of the present invention.
[0014] The organic electroluminescent device provided by the present invention has a charge generation layer material of a substituted phenanthroline compound, which has a high efficiency charge generation capability, can effectively improve the luminous efficiency of the organic electroluminescent device, and has a shallow energy level, can be used in combination with adjacent layer materials, effectively improves the charge transfer performance of the organic electroluminescent device, improves the luminous efficiency of the organic electroluminescent device, reduces its driving voltage and prolongs its service life. The display device provided by the present invention has an excellent display effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a schematic diagram of the structure of a typical organic electroluminescent device;
[0016] Figure numerals: 20, organic electroluminescent device; 21, substrate; 22, reflective anode; 231, first hole injection layer; 241, first hole transport layer; 251, first light-emitting layer; 261, first electron transport layer; 27, charge generation layer; 232, second hole injection layer; 242, second hole transport layer; 252, second light-emitting layer; 262, second electron transport layer; 28, electron injection layer; 29, cathode electrode. DETAILED DESCRIPTION
[0017] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.
[0018] The first aspect of the present invention provides an organic electroluminescent device, the organic electroluminescent device comprising a charge generation layer and an electron transport layer, the charge generation layer material comprising a compound of formula (I):
[0019]
[0020] in,
[0021] R 1 ,R 2 is selected from hydrogen, unsubstituted or Rc-substituted C 6 -C 30 Aryl, unsubstituted or Rc-substituted C 3 -C 30 heteroaryl;
[0022] Ar 1 Selected from C containing N atom which is unsubstituted or substituted by Rc 3 -C 30 heteroarylene;
[0023] L 1 , L 2 Selected from chemical bonds, unsubstituted or Rc-substituted C 6 -C 30 Arylene, unsubstituted or Rc-substituted C 5 -C 30 heteroaryl;
[0024] The heteroatoms on the heteroaryl or heteroarylene group are each independently selected from O, S or N;
[0025] The substituents Rc of each group are independently selected from hydrogen, deuterium, halogen, nitro, cyano, C 1 -C 4 Alkyl, phenyl, biphenyl, terphenyl, pyridyl, pyrimidinyl or naphthyl.
[0026] Preferably, R 1 and R 2 are each independently selected from hydrogen, C unsubstituted or substituted by Rc 6 -C 18 Aryl, unsubstituted or Rc-substituted C 3 -C 18 Heteroaryl.
[0027] Preferably, Ar1 Selected from C containing N atom which is unsubstituted or substituted by Rc 3 -C 18 Heteroarylene.
[0028] Preferably, L 1 , L 2 Selected from chemical bonds, unsubstituted or Rc-substituted C 6 -C 18 Arylene, unsubstituted or Rc-substituted C 3 -C 18 Heteroaryl.
[0029] More preferably, R 1 and R 2 A group each independently selected from the following compounds which are hydrogen, unsubstituted or substituted with Rc: benzene, biphenyl, terphenyl, naphthalene, phenanthrene, triphenylene, fluorene, anthracene, pyridine, pyridazine, pyrimidine, pyrazine, quinoline, isoquinoline, quinazoline, quinoxaline, cinnoline, naphthyridine, triazine, phenanthroline, phenylbipyridyl, pyridopyrazine, furan, benzofuran, dibenzofuran, aza-dibenzofuran, benzothiophene, dibenzothiophene, aza-dibenzothiophene, 9,9-dimethylfluorene, 9,9-diphenylfluorene, spirofluorene.
[0030] More preferably, Ar 1 A group selected from the following compounds which are unsubstituted or substituted with Rc: benzene, biphenyl, terphenyl, naphthalene, phenanthrene, triphenylene, fluorene, anthracene, dibenzofuran, dibenzothiophene, 9,9-dimethylfluorene, 9,9-diphenylfluorene, spirofluorene.
[0031] More preferably, L 1 , L 2 A subunit selected from the following compounds which are chemically bonded, unsubstituted or substituted by Rc: benzene, biphenyl, terphenyl, naphthalene, phenanthrene, triphenylene, fluorene, anthracene, 9,9-dimethylfluorene, 9,9-diphenylfluorene, spirofluorene.
[0032] In some embodiments of the present invention, the charge generation layer material includes Li or Yb, and the content of Li or Yb is 0.5%-2.5% of the charge generation layer material by mass percentage.
[0033] In some embodiments of the present invention, the charge generation layer has a thickness of 10 nm to 30 nm.
[0034] In some embodiments of the present invention, the thickness of the electron transport layer is 10 nm-40 nm.
[0035] In some embodiments of the present invention, the electron transport layer material includes LiQ, and the mass percentage of LiQ is 30%-70% based on the mass of the electron transport layer material.
[0036] In some embodiments of the present invention, the compound of formula (I) may be selected from the following compounds A1 to A30:
[0037]
[0038]
[0039] The present invention provides an organic electroluminescent device, which comprises at least one of the charge generation layer materials provided by the present invention. The charge generation material provided by the present invention has a highly efficient charge generation capability, and when used in combination with the electron transport material provided by the present invention, it can effectively improve the charge transport performance of the organic electroluminescent device, improve the luminous efficiency of the organic electroluminescent device, reduce its driving voltage and extend its service life. Therefore, the organic electroluminescent device provided by the present invention has a low driving voltage, high luminous efficiency and a long service life.
[0040] In the present invention, there is no particular limitation on the type and structure of the organic electroluminescent device, and it can be an organic electroluminescent device of different types and structures known in the art, as long as at least one of the charge generating materials and at least one of the electron transporting materials provided by the present invention can be used.
[0041] In one embodiment of the present invention, an organic electroluminescent device comprises an anode and a cathode, m light-emitting units are stacked between the anode and the cathode, and (m-1) charge generation layers are stacked between two adjacent light-emitting units, and each charge generation layer comprises an n-type charge generation layer and a p-type charge generation layer, wherein m is an integer ≥2; each light-emitting unit comprises at least one light-emitting layer, and the maximum emission wavelength of light emitted in different light-emitting units is different; at least one of the n-type charge generation layers comprises at least one compound represented by formula (I) and a metal-containing material, and the metal-containing material comprises a metal, a metal complex or a combination thereof.
[0042] In one embodiment of the present invention, the light-emitting unit in the organic electroluminescent device may include a first light-emitting unit and a second light-emitting unit, and the two light-emitting units may be the same or different; the charge generation layer may be arranged between the first light-emitting unit and the second light-emitting unit, the first light-emitting unit may be arranged between the anode and the charge generation layer, and the second light-emitting unit may be arranged between the charge generation layer and the cathode, the n-type charge generation layer of the charge generation layer may include at least one compound represented by formula (I) and a metal-containing material, and the second light-emitting unit may also include an electron transport layer between the light-emitting layer of the second light-emitting unit and the cathode.
[0043] In one embodiment of the present invention, in an organic electroluminescent device having 2 light-emitting units (m=2), the first light-emitting unit may further include a HT-light-emitting auxiliary layer between the light-emitting layer of the first light-emitting unit and the anode.
[0044] In other embodiments of the present invention, the organic electroluminescent device of the present invention may be a light-emitting device with a top-emitting structure, which may include an anode, a first light-emitting unit, a charge generation layer, a second light-emitting unit, an electron injection layer, and a transparent or semi-transparent cathode in sequence on a substrate.
[0045] The organic electroluminescent device of the present invention may also be a bottom-emitting structure light-emitting device, which may include a transparent or semi-transparent anode, a first light-emitting unit, a charge generation layer, a second light-emitting unit, an electron injection layer, and a cathode in sequence on a substrate.
[0046] The organic electroluminescent device of the present invention may also be a light-emitting device with a double-sided light-emitting structure, which may include a transparent or semi-transparent anode, a first light-emitting unit, a charge generating layer, a second light-emitting unit, an electron injection layer, and a transparent or semi-transparent cathode in sequence on a substrate.
[0047] The first light-emitting unit includes a first hole injection layer, a first hole transport layer, a first light-emitting layer and a first electron transport layer arranged in sequence, and the second light-emitting unit includes a second hole injection layer, a second hole transport layer, a second light-emitting layer and a second electron transport layer arranged in sequence.
[0048] In addition, the organic electroluminescent device of the present invention may have an electron blocking layer between the hole transport layer and the light-emitting layer, may have a hole blocking layer between the light-emitting layer and the electron transport layer, and a light extraction layer may be provided on the transparent electrode on the light-emitting side. However, the structure of the organic electroluminescent device of the present invention is not limited to the above-mentioned specific structure, and the above-mentioned layers may be omitted or increased if necessary. The present invention has no particular restrictions on the thickness of the above-mentioned anode, hole injection layer, hole transport layer, electron blocking layer, light-emitting layer, hole blocking layer, electron injection layer, cathode and light extraction layer, as long as the purpose of the present invention can be achieved. For example, an organic electroluminescent device may include, on a substrate, an anode (100 nm to 150 nm) made of a metal, a first hole injection layer (5 nm to 20 nm), a first hole transport layer (80 nm to 140 nm), an electron blocking layer (5 nm to 20 nm), a first light-emitting layer (15 nm to 40 nm), a hole blocking layer (5 nm to 20 nm), a first electron transport layer (10 nm to 40 nm), a charge generation layer (10 nm to 30 nm), a second hole injection layer (5 nm to 20 nm), a second hole transport layer (80 nm to 140 nm), a second light-emitting layer (15 nm to 40 nm), a second electron transport layer (10 nm to 40 nm), an electron injection layer (5 nm to 20 nm), a transparent or semi-transparent cathode, and a light extraction layer (50 nm to 90 nm). Exemplarily, Figure 1 A schematic diagram of a typical organic electroluminescent device 20 is shown, wherein, from bottom to top, a substrate 21, a reflective anode 22, a first hole injection layer 231, a first hole transport layer 241, a first light-emitting layer 251, a first electron transport layer 261, a charge generation layer 27, a second hole injection layer 232, a second hole transport layer 242, a second light-emitting layer 252, a second electron transport layer 262, an electron injection layer 28, and a cathode electrode 29 are sequentially arranged. It can be understood that Figure 1 Only a typical structure of an organic electroluminescent device is schematically shown, and the present invention is not limited to this structure. The charge generation layer material or electron transport layer material of the present invention can be used in any type of organic electroluminescent device.
[0049] For convenience, the organic electroluminescent device of the present invention is described below, but this does not mean any limitation on the protection scope of the present invention. It is understood that all organic electroluminescent devices using the charge generation layer material or electron transport layer material of the present invention are within the protection scope of the present invention.
[0050] In the present invention, there is no particular limitation on the substrate 21 , and conventional substrates used in organic electroluminescent devices in the prior art may be used, such as glass, polymer materials, and glass and polymer materials with thin film transistor (TFT) components.
[0051] In the present invention, there is no particular limitation on the material of the reflective anode 22, and the reflective anode 22 may be selected from indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO 2 ), zinc oxide (ZnO) and other transparent conductive materials, and can also be selected from metal materials such as silver and its alloys, aluminum and its alloys, and can also be selected from organic conductive materials such as poly 3,4-ethylenedioxythiophene (PEDOT), or the reflective anode 22 is a multilayer structure formed by the above materials. The present invention has no particular restriction on the number of layers of the multilayer structure, and can be selected according to actual needs, as long as it can meet the purpose of the present invention, for example, 1 layer, 2 layers, 3 layers or more layers.
[0052] In the present invention, there is no particular limitation on the materials of the first hole injection layer 231 and the second hole injection layer 232, and they can be made of hole injection layer materials known in the art or hole transport layer materials (HTM) known in the art. For example, at least one of the known hole transport layer materials (HTM) is selected as the hole injection layer material.
[0053] In the present invention, the first hole injection layer 231 and the second hole injection layer 232 may further include a p-type dopant. The present invention has no particular limitation on the type of the p-type dopant, and various p-type dopants known in the art may be used. For example, the p-type dopant may be selected from but not limited to at least one of the following p-1 to p-3 compounds:
[0054]
[0055] In the present invention, there is no particular limitation on the amount of the p-type dopant, which may be an amount known to those skilled in the art.
[0056] In the present invention, there is no particular limitation on the materials of the first hole transport layer 241 and the second hole transport layer 242, and they can be made of hole transport layer materials (HTM) known in the art. The present invention does not particularly limit the number of hole transport layers, and can be adjusted according to actual needs, as long as the purpose of the present invention can be met, for example, 1 layer, 2 layers, 3 layers, 4 layers or more layers.
[0057] For example, the HTM for the hole injection layer material and the HTM for the hole transport layer material may be selected from, but not limited to, at least one of the following HT-1 to HT-31 compounds:
[0058]
[0059]
[0060]
[0061] In the present invention, there is no particular restriction on the materials of the first light-emitting layer 251 and the second light-emitting layer 252, and they may each contain a light-emitting layer host material and a light-emitting layer guest material. There is no particular restriction on the amounts of the light-emitting layer host material and the light-emitting layer guest material, and they may be amounts known to those skilled in the art.
[0062] In the present invention, the light-emitting layer may include a blue light-emitting layer, a green light-emitting layer or a red light-emitting layer. The light-emitting material in the light-emitting layer is not particularly limited, and various light-emitting materials known to those skilled in the art can be used.
[0063] In the present invention, there is no particular limitation on the main material of the light-emitting layer, and at least one of the main materials of the light-emitting layer known in the art can be used. For example, it can be selected from but not limited to at least one of the following BH-1 to BH-10 compounds:
[0064]
[0065] In the present invention, there is no particular limitation on the guest material of the light-emitting layer, and at least one of the light-emitting layer guest materials known in the art can be used. For example, the light-emitting layer guest material can be selected from but not limited to at least one of the following BD-1 to BD-9 compounds:
[0066]
[0067] In the present invention, the first electron transport layer 261 and the second electron transport layer 262 include at least one of the electron transport layer materials of the present invention, and may also include a combination of at least one of the electron transport layer materials of the present invention and at least one of the known electron transport materials. There is no particular limitation on the number of layers of the electron transport layer, and it can be adjusted according to actual needs, as long as it can meet the purpose of the present invention, for example, 1 layer, 2 layers, 3 layers, 4 layers or more layers.
[0068] For example, the known electron transport material may be selected from, but not limited to, at least one of the following ET-1 to ET-57 compounds:
[0069]
[0070]
[0071]
[0072]
[0073] In the present invention, the first electron transport layer 261 and the second electron transport layer 262 may each include an n-type dopant. There is no particular limitation on the type of the n-type dopant, and various n-type dopants known in the art may be used. For example, the following n-type dopant 8-hydroxyquinoline lithium (LiQ) may be used:
[0074]
[0075] In the present invention, there is no particular limitation on the amount of the n-type dopant, and it can be an amount known to those skilled in the art.
[0076] In the present invention, the charge generation layer 27 may include at least one of the charge generation layer materials of the present invention, or may include a combination of at least one of the charge generation layer materials of the present invention and at least one of the known charge generation materials.
[0077] For example, the known charge generating material may be selected from, but not limited to, at least one of the following CGL00R1 to CGL00R5 compounds:
[0078]
[0079] In the present invention, there is no particular limitation on the material of the electron injection layer 28, and any electron injection layer material known in the art may be used, for example, including but not limited to 8-hydroxyquinoline lithium (LiQ), LiF, NaCl, CsF, Li 2 O、Cs 2 CO 3 , BaO, Na, Li, Ca and other materials.
[0080] In the present invention, there is no particular limitation on the material of the cathode electrode 29, which may be selected from but not limited to magnesium-silver mixture, LiF / Al, ITO, Al and other metals, metal mixtures, oxides and the like.
[0081] The method for preparing the organic electroluminescent device of the present invention is not particularly limited, and any method known in the art may be used. For example, the present invention may be prepared by the following preparation method:
[0082] The method for preparing the organic electroluminescent device of the present invention may also include but is not limited to the following steps:
[0083] (1) cleaning the reflective anode 22 on the top-emitting organic electroluminescent device substrate 21 by using a cleaning machine through steps such as chemical cleaning, water cleaning, brushing, high-pressure water cleaning, and air knife cleaning, and then heating treatment;
[0084] (2) vacuum evaporating a hole injection material on the reflective anode 22 to form a first hole injection layer 231;
[0085] (3) vacuum evaporating a hole transport layer material on the first hole injection layer 231 to form a first hole transport layer 241;
[0086] (4) vacuum evaporating a first light-emitting layer 251 on the first hole transport layer 241, wherein the light-emitting layer includes a light-emitting layer host material and a light-emitting layer guest material;
[0087] (5) vacuum evaporating an electron transport material on the first light-emitting layer 251 to form a first electron transport layer 261;
[0088] (6) vacuum evaporating a charge generating material on the first electron transport layer 261 to form the charge generating layer 27;
[0089] (7) vacuum evaporating a hole injection material on the charge generation layer 27 to form a second hole injection layer 232;
[0090] (8) vacuum evaporating a hole transport layer material on the second hole injection layer 232 to form a second hole transport layer 242;
[0091] (9) vacuum evaporating a second light-emitting layer 252 on the second hole transport layer 242, wherein the light-emitting layer includes a light-emitting layer host material and a light-emitting layer guest material;
[0092] (10) vacuum evaporating an electron transport material on the second light emitting layer 252 to form a second electron transport layer 262;
[0093] (11) vacuum evaporating an electron injection material on the second electron transport layer 262 to form the electron injection layer 28;
[0094] (12) A cathode material is vacuum-deposited on the electron injection layer 28 to form the cathode 29 .
[0095] The above only describes a typical structure of an organic electroluminescent device and its preparation method. It should be understood that the present invention is not limited to this structure. The charge generation layer material or electron transport layer material of the present invention can be used in an organic electroluminescent device of any structure, and the organic electroluminescent device can be prepared by any preparation method known in the art.
[0096] The second aspect of the present invention provides a display device, which includes the organic electroluminescent device provided by the first aspect of the present invention. The display device includes but is not limited to a display, a television, a tablet computer, a mobile communication terminal, etc.
[0097] The synthesis method of the compound of the present invention is not particularly limited, and any method known to those skilled in the art can be used for synthesis. The following examples illustrate the synthesis process of the compound of the present invention.
[0098] Synthesis example
[0099] Synthesis of compound A1:
[0100]
[0101] 100mmol 3-bromo-5-chloro-1,1'-biphenyl was dissolved in 800mL tetrahydrofuran, cooled to -78°C, 105mmol n-butyllithium was added dropwise, and the temperature was kept for 30min. Then 110mmol triisopropyl borate was added dropwise. After the addition was completed, the temperature was naturally raised to room temperature. 1000ml water was added to the reaction solution, and the organic layer was separated. The organic layer was dried and concentrated to obtain a white solid M1.
[0102] In a reaction flask, 100 mmol of M1, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M2. 3 ) 4 The added amount is 1 mol% of M1.
[0103] 100 mmol of 2-bromophenanthroline, 100 mmol of p-chlorophenylboric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain white powder M3. Among them, Pd(PPh 3 ) 4 The amount of addition is 1 mol% of 2-bromophenanthroline.
[0104] In the reaction flask, 100 mmol of M3, 100 mmol of biboric acid pinacol ester, 41.4 g of potassium carbonate (300 mmol), 800 mL of dioxane, and 1 mol% of Pd(PPh 3 ) 4 , react at 100°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M4. 3 )4 The added amount is 1 mol% of M3.
[0105] 100 mmol of M2, 100 mmol of M4, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder A1. 3 ) 4 The amount added is 1 mol% of M2.
[0106] 1 H NMR(400MHz,Chloroform)δ8.80(d,J=8.0Hz,2H),8.71(d,J=8.8Hz,3H),8.45(t,J=7.6Hz,3H),8.40(d,J=8 .0Hz,2H),8.22(s,1H),7.92-7.83(m,4H),7.75(d,J=8.0Hz,2H),7.33–7.37(m,7H),7.32(d,J=8.4Hz,2H),.
[0107] Synthesis of compound A3:
[0108]
[0109] 100mmol 3-bromo-5-chloro-1,1'-biphenyl was dissolved in 800mL tetrahydrofuran, cooled to -78°C, 105mmol n-butyllithium was added dropwise, and the temperature was kept for 30min. Then 110mmol triisopropyl borate was added dropwise. After the addition was completed, the temperature was naturally raised to room temperature. 1000ml water was added to the reaction solution, and the organic layer was separated. The organic layer was dried and concentrated to obtain a white solid M1.
[0110] In a reaction flask, 100 mmol of M1, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M2. 3 )4 The added amount is 1 mol% of M1.
[0111] 100 mmol of 4-chloro-2,9-dimethylphenanthroline, 100 mmol of p-chlorophenylboronic acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain white powder M3. Among them, Pd(PPh 3 ) 4 The amount of addition was 1 mol% of 4-chloro-2,9-dimethylphenanthroline.
[0112] In the reaction flask, 100 mmol of M3, 100 mmol of biboric acid pinacol ester, 41.4 g of potassium carbonate (300 mmol), 800 mL of dioxane, and 1 mol% of Pd(PPh 3 ) 4 , react at 100°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M4. 3 ) 4 The added amount is 1 mol% of M3.
[0113] 100 mmol of M2, 100 mmol of M4, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder A3. 3 ) 4 The amount added is 1 mol% of M2.
[0114] 1H NMR(400MHz,Chloroform)δ8.79(d,J=7.2Hz,1H),8.65(s,1H),8.53(s,1H),8.46( d,J=6.0Hz,1H),8.40(d,J=6.4Hz,1H),8.22(s,1H),8.06(d,J=7.6Hz,1H),7.88(d ,J=7.2Hz,1H),7.75(d,J=8.4Hz,2H),7.69(d,J=8.8Hz,1H),7.61-7.36(m,7H),7. 35(d,J=7.6Hz,1H),7.28(d,J=7.6Hz,1H),7.25(s,4H),2.76(s,3H),2.69(s,3H).
[0115] Synthesis of compound A5:
[0116]
[0117] 100 mmol of 8-bromoquinoline, 100 mmol of p-chlorophenylboric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M1. 3 ) 4 The amount of addition was 1 mol% of 8-bromoquinoline.
[0118] In the reaction flask, 100 mmol of M1, 100 mmol of biboric acid pinacol ester, 41.4 g of potassium carbonate (300 mmol), 800 mL of dioxane, and 1 mol% of Pd (PPh 3 ) 4 , react at 100°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and the obtained solid is recrystallized and purified with toluene to obtain white powder M2. 3 ) 4 The added amount is 1 mol% of M1.
[0119] In a reaction flask, 100 mmol of M2, 100 mmol of 3-bromo-5-chloro-1,1'-biphenyl, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain white powder M3. Among them, Pd(PPh 3 ) 4 The amount of addition was 1 mol% of 3-bromo-5-chloro-1,1'-biphenyl.
[0120] 100 mmol of 2-bromophenanthroline, 100 mmol of p-chlorophenylboric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain white powder M4. Among them, Pd(PPh 3 ) 4 The amount of addition is 1 mol% of 2-bromophenanthroline.
[0121] In the reaction flask, 100 mmol of M4, 100 mmol of biboric acid pinacol ester, 41.4 g of potassium carbonate (300 mmol), 800 mL of dioxane, and 1 mol% of Pd(PPh 3 ) 4 , react at 100°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M5. 3 ) 4 The added amount is 1 mol% of M4.
[0122] 100 mmol of M3, 100 mmol of M5, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain a white powder A5. Among them, Pd(PPh 3 ) 4 The added amount is 1 mol% of M3.
[0123] 1 H NMR(400MHz,Chloroform)δ8.86(t,J=7.2Hz,2H),8.70(d,J=8.0Hz,2H),8.45(d,J=6.8Hz,1H),8.3 9(d,J=6.8Hz,1H),8.25–8.16(m,4H),7.86(t,J=8.0Hz,3H),7.80-7.72(m,3H),7.66–7.24(m,13H).
[0124] Synthesis of compound A8:
[0125]
[0126] 100 mmol 1-bromo-3,5-dichlorobenzene was dissolved in 800 mL tetrahydrofuran, cooled to -78°C, 105 mmol n-butyl lithium was added dropwise, and the temperature was kept for 30 min. Then 110 mmol triisopropyl borate was added dropwise. After the addition was completed, the temperature was naturally raised to room temperature. 1000 ml water was added to the reaction solution, and the organic layer was separated. The organic layer was dried and concentrated to obtain a white solid M1.
[0127] In a reaction flask, 100 mmol of M1, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M2. 3 ) 4 The added amount is 1 mol% of M1.
[0128] 100 mmol of 2-bromo-5-chloropyridine, 100 mmol of phenylboric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain white powder M3. Among them, Pd(PPh 3 ) 4 The amount of addition was 1 mol% of 2-bromo-5-chloropyridine.
[0129] In the reaction flask, 100 mmol of M3, 100 mmol of biboric acid pinacol ester, 41.4 g of potassium carbonate (300 mmol), 800 mL of dioxane, and 1 mol% of Pd(PPh 3 ) 4 , react at 100°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M4. 3 ) 4 The added amount is 1 mol% of M3.
[0130] 100 mmol of M2, 200 mmol of M4, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 2 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain a white powder A8. Among them, Pd(PPh 3 ) 4 The amount added is 2 mol% of M2.
[0131] 1 H NMR(400MHz,Chloroform)δ8.95(s,2H),8.85(d,J=7.2Hz,1H),8.60(s,2H),8.44(d,J=6.4Hz,1H),8.38(d,J=6.4Hz,1H), 8.32(d,J=7.6Hz,4H),8.21(s,1H),8.00(t,J=8.4Hz,4H),7.88(d,J=7.2Hz,1H),7.60–7.47(m,8H),7.32(d,J=8.4Hz,1H).
[0132] Synthesis of compound A10:
[0133]
[0134] 100 mmol of 2-bromo-5-chloropyridine, 100 mmol of phenylboric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M1. 3 ) 4 The amount of addition was 1 mol% of 2-bromo-5-chloropyridine.
[0135] In the reaction flask, 100 mmol of M1, 100 mmol of biboric acid pinacol ester, 41.4 g of potassium carbonate (300 mmol), 800 mL of dioxane, and 1 mol% of Pd (PPh 3 ) 4 , react at 100°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and the obtained solid is recrystallized and purified with toluene to obtain white powder M2. 3 ) 4 The added amount is 1 mol% of M1.
[0136] 100 mmol of M2, 100 mmol of m-chlorobromobenzene, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain white powder M3. Among them, Pd(PPh 3 ) 4 The amount added is 1 mol% of M2.
[0137] 100 mmol of 2,9-dichloro-1,10-phenanthroline, 100 mmol of phenylboric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF and 200 mL of water were added to the reaction flask, and 1 mol% of Pd(PPh 3 ) 4, react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M4. 3 ) 4 The amount of addition was 1 mol% of 2,9-dichloro-1,10-phenanthroline.
[0138] 100 mmol of M4, 100 mmol of p-chlorophenylboric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain white powder M5. Among them, Pd(PPh 3 ) 4 The added amount is 1 mol% of M4.
[0139] In the reaction flask, 100 mmol of M5, 100 mmol of biboric acid pinacol ester, 41.4 g of potassium carbonate (300 mmol), 800 mL of dioxane, and 1 mol% of Pd(PPh 3 ) 4 , react at 100°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M6. 3 ) 4 The added amount is 1 mol% of M5.
[0140] In a reaction flask, 100 mmol of M3, 100 mmol of M6, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder A10. 3 ) 4 The added amount is 1 mol% of M3.
[0141] 1H NMR(400MHz,Chloroform)δ8.93(s,1H),8.69(d,J=8.4Hz,2H),8.40(d,J=6.8Hz,2H),8.34(d,J=7.2Hz ,4H),8.12(s,1H),8.01(d,J=8.0Hz,1H),7.95–7.84(m,4H),7.71-7.46(m,10H),7.34(d,J=8.4Hz,2H).
[0142] Synthesis of compound A16:
[0143]
[0144] 100mmol 3-bromo-5-chloro-1,1'-biphenyl was dissolved in 800mL tetrahydrofuran, cooled to -78°C, 105mmol n-butyllithium was added dropwise, and the temperature was kept for 30min. Then 110mmol triisopropyl borate was added dropwise. After the addition was completed, the temperature was naturally raised to room temperature. 1000ml water was added to the reaction solution, and the organic layer was separated. The organic layer was dried and concentrated to obtain a white solid M1.
[0145] In a reaction flask, 100 mmol of M1, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M2. 3 ) 4 The added amount is 1 mol% of M1.
[0146] In the reaction flask, 100 mmol of M2, 100 mmol of biboric acid pinacol ester, 41.4 g of potassium carbonate (300 mmol), 800 mL of dioxane, and 1 mol% of Pd (PPh 3 ) 4 , react at 100°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M3. 3 ) 4 The amount added is 1 mol% of M2.
[0147] 100 mmol of M3, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain a white powder A16. Among them, Pd(PPh 3 ) 4 The added amount is 1 mol% of M3.
[0148] 1 H NMR(400MHz,Chloroform)δ8.98(s,1H),8.80(d,J=7.2Hz,2H),8.60(s,2H),8.46(d,J=6.4Hz,2H),8.40 (d,J=7.6Hz,2H),7.88(d,J=8.0Hz,2H),7.75(d,J=7.2Hz,2H),7.60-7.36(m,7H),7.35(d,J=8.0Hz,2H).
[0149] Synthesis of compound A25:
[0150]
[0151] In a reaction flask, 100 mmol of 1-bromo-3-chloro-5-iodobenzene, 100 mmol of 4-quinolineboric acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M1. 3 ) 4 The amount of addition is 1 mol% of 2-bromophenanthroline.
[0152] 100 mmol M1 was dissolved in 800 mL tetrahydrofuran, cooled to -78°C, 105 mmol n-butyl lithium was added dropwise, and the temperature was kept for 30 min. Then 110 mmol triisopropyl borate was added dropwise. After the addition was completed, the temperature was naturally raised to room temperature. 1000 ml water was added to the reaction solution, and the organic layer was separated. The organic layer was dried and concentrated to obtain a white solid M2.
[0153] 100 mmol of M2, 100 mmol of 2-bromophenanthroline, 41.4 g of potassium carbonate (300 mmol), 800 mL of tetrahydrofuran (THF) and 200 mL of water were added to the reaction flask, and 1 mol% of tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), reacted at 60°C for 12h. After the reaction was completed, the reaction was stopped, and the reactant was cooled to room temperature, added with water, filtered, washed with water, and the obtained solid was recrystallized and purified with toluene to obtain white powder M3. Among them, Pd(PPh 3 ) 4 The amount added is 1 mol% of M2.
[0154] 100 mmol of 2-chloro-4,6-diphenylpyrimidine, 100 mmol of p-chlorophenylboronic acid, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF and 200 mL of water were added to the reaction flask, and 1 mol% of Pd(PPh 3 ) 4 , react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M4. 3 ) 4 The amount of addition was 1 mol% of 2-chloro-4,6-diphenylpyrimidine.
[0155] In the reaction flask, 100 mmol of M4, 100 mmol of biboric acid pinacol ester, 41.4 g of potassium carbonate (300 mmol), 800 mL of dioxane, and 1 mol% of Pd(PPh 3 ) 4 , react at 100°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder M5. 3 ) 4 The added amount is 1 mol% of M4.
[0156] 100 mmol of M3, 100 mmol of M5, 41.4 g of potassium carbonate (300 mmol), 800 mL of THF and 200 mL of water were added to the reaction flask, and 1 mol% of Pd(PPh 3 ) 4 , react at 60°C for 12h. After the reaction is completed, stop the reaction, cool the reactant to room temperature, add water, filter, wash with water, and purify the obtained solid by recrystallization with toluene to obtain white powder A25. 3 )4 The added amount is 1 mol% of M3.
[0157] 1 H NMR(400MHz,Chloroform)δ8.91(d,J=7.2Hz,1H),8.82(d,J=6.8Hz,1H),8.65 (t,J=7.2Hz,1H),8.54(t,J=7.2Hz,1H),8.45(d,J=7.6Hz,1H),8.41(d,J=7.2H z,1H),8.25–8.15(m,3H),8.01-7.90(m,6H),7.88(d,J=7.2Hz,1H),7.81(d,J= 7.2Hz,1H),7.65–7.45(m,11H),7.35(d,J=8.0Hz,1H),7.22(d,J=8.4Hz,2H),.
[0158] Other compounds of the present invention can be synthesized by selecting appropriate raw materials according to the ideas of the above synthesis examples, or by selecting any other appropriate method and raw materials for synthesis.
[0159] Example 1
[0160] A glass substrate coated with a 150nm thick ITO transparent conductive layer is ultrasonically treated in a cleaning agent, rinsed in deionized water, ultrasonically degreased in an acetone-ethanol mixed solvent, baked in a clean environment until the water is completely removed, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam to obtain a glass substrate with an anode;
[0161] Then, the glass substrate with the anode is placed in a vacuum chamber and evacuated to less than 10 -5 A first hole injection layer is vacuum-deposited on the anode layer film of the glass substrate with an anode. The materials of the first hole injection layer include hole injection layer material HT-11 and p-type dopant p-1. The deposition is performed by a multi-source co-evaporation method. The deposition rate of the hole injection layer material HT-11 is adjusted to 0.1 nm / s, the deposition rate of the p-type dopant p-1 is adjusted to 3% of the deposition rate of the hole injection layer material HT-11, and the total deposition film thickness is 10 nm. The hole injection layer material HT-11 and the p-type dopant p-1 are as follows:
[0162]
[0163] Then, a hole transport layer material HT-5 was vacuum-deposited on the first hole injection layer as the first hole transport layer, wherein the evaporation rate was 0.1 nm / s, the evaporation film thickness was 80 nm, and the hole transport layer material HT-5 was as follows:
[0164]
[0165] Then, a first light-emitting layer is vacuum-deposited on the first hole transport layer. The first light-emitting layer includes a light-emitting layer main material BH-2 and a light-emitting layer guest material BD-1. The deposition is performed by a multi-source co-evaporation method. The deposition rate of the light-emitting layer main material BH-2 is adjusted to 0.1 nm / s, the deposition rate of the light-emitting layer guest material BD-1 is adjusted to 3% of the deposition rate of the light-emitting layer main material BH-2, and the deposition film thickness is 30 nm. The light-emitting layer main material BH-2 and the light-emitting layer guest material BD-1 are as follows:
[0166]
[0167] Then, a first electron transport layer is vacuum-deposited on the first light-emitting layer. The materials of the first electron transport layer are compound ET6 and LiQ. The evaporation rate of compound ET6 is 0.1 nm / s, the evaporation rate ratio of compound ET6 and LiQ is 5:5, and the total evaporation film thickness is 30 nm. Compound ET6 and LiQ are as follows:
[0168]
[0169] The first hole injection layer, the first hole transport layer, the first light-emitting layer and the first electron transport layer together constitute a first light-emitting unit;
[0170] On the topmost first electron transport layer of the first light-emitting unit, the compound A1 provided by the present invention and metal ytterbium (Yb) are evaporated to form a charge generation layer, wherein the evaporation rate of the compound A1 is 0.01 nm / s, the evaporation rate ratio of the compound A1 to Yb is 99:1, and the total evaporation film thickness is 10 nm;
[0171] A second hole injection layer is evaporated on the charge generation layer, wherein the material of the second hole injection layer includes hole injection layer material HT-11 and p-type dopant p-1, wherein the evaporation rate of the hole injection layer material HT-11 is adjusted to 0.1 nm / s, the evaporation rate ratio of the hole injection layer material HT-11 to the p-type dopant p-1 is 99:1, and the total evaporation film thickness is 10 nm;
[0172] Then, a hole transport layer material HT-5 was vacuum-deposited on the second hole injection layer as the second hole transport layer, wherein the evaporation rate was 0.1 nm / s and the evaporation film thickness was 80 nm;
[0173] Then, a second light-emitting layer is vacuum-evaporated on the second hole transport layer, wherein the second light-emitting layer includes a light-emitting layer main material BH-2 and a light-emitting layer guest material BD-1, and the evaporation is performed by a multi-source co-evaporation method, wherein the evaporation rate of the light-emitting layer main material BH-2 is adjusted to 0.1 nm / s, the evaporation rate of the light-emitting layer guest material BD-1 is 3% of the evaporation rate of the light-emitting layer main material BH-2, and the total evaporation film thickness is 30 nm;
[0174] Then, a second electron transport layer is vacuum evaporated on the second light-emitting layer, wherein the electron transport materials are compound ET6 and LiQ, wherein the evaporation rate of compound ET6 is 0.1 nm / s, the evaporation rate ratio of compound ET6 and LiQ is 5:5, and the total evaporation film thickness is 30 nm;
[0175] The second hole injection layer, the second hole transport layer, the second light-emitting layer and the second electron transport layer together constitute a second light-emitting unit;
[0176] Then, LiF with a thickness of 0.5 nm is vacuum-deposited on the second electron transport layer at the top of the second light-emitting unit as an electron injection layer, wherein the evaporation rate is 0.1 nm / s;
[0177] Finally, an Al layer with a thickness of 150 nm was vacuum evaporated on the electron injection layer as a cathode electrode of the organic electroluminescent device, wherein the evaporation rate was 0.1 nm / s.
[0178] Embodiment 2-7
[0179] Except that the charge generation layer material is replaced by A3, A6, A8, A11, A18, A19 respectively, the rest is the same as Example 1. See Table 1 for details.
[0180] Comparative Example 1
[0181] Except that the charge generation layer material is CGL00R1 instead of A1, the rest is the same as Example 1. CGL00R1 is as follows:
[0182]
[0183] Comparative Example 2
[0184] Except that the charge generation layer material is CGL00R4 instead of A1, the rest is the same as Example 1. CGL00R4 is as follows:
[0185]
[0186] The organic electroluminescent device prepared by the above process was subjected to the following performance tests:
[0187] At the same brightness, the driving voltage, current efficiency and device life of the organic electroluminescent devices prepared in Examples 1 to 7 and Comparative Examples 1 to 2 were measured using a digital source meter and a brightness meter. Specifically, the voltage was increased at a rate of 0.1 V per second, and the brightness of the organic electroluminescent device was measured when it reached 1000 cd / m 2 The voltage at which the light is on is the driving voltage, and the current density at this time is measured at the same time; the ratio of brightness to current density is the current efficiency; the life test of LT95 is as follows: use a brightness meter at 1000cd / m 2 At the same brightness, the current is kept constant and the brightness of the organic electroluminescent device is measured to drop to 950cd / m 2 The time is in hours. The results are shown in Table 1.
[0188] Table 1 Performance results of organic electroluminescent devices
[0189]
[0190]
[0191] As can be seen from Table 1, the organic electroluminescent devices prepared in Examples 1 to 7 use the compounds A1, A3, A5, A8, A10, A16, and A25 provided by the present invention as the first charge generation layer material. Compared with the use of known materials in the prior art as the charge generation layer material of the organic electroluminescent device in Comparative Examples 1 and 2, the organic electroluminescent device of the present invention has a lower driving voltage, a higher current efficiency, and a longer LT95 life. Thus, it is explained that when the compound of formula (I) is used as a charge generation material in an organic electroluminescent device, the driving voltage can be effectively reduced, the current efficiency can be improved, and the service life of the device can be extended. The material of the present invention has a significant performance improvement in terms of improving the efficiency of the organic electroluminescent device and extending the life of the organic electroluminescent device, and an organic electroluminescent device with good performance can be obtained.
[0192] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An organic electroluminescent device comprising a charge generation layer and an electron transport layer, characterized in that: The charge generation layer material comprises a compound of formula (I): in, R 1 ,R 2 is selected from hydrogen, unsubstituted or Rc-substituted C6-C 30 Aryl, unsubstituted or Rc-substituted C3-C 30 heteroaryl; Ar 1 Selected from C3-C containing N atom which is unsubstituted or substituted by Rc 30 heteroarylene; L 1 , L 2 Selected from chemical bonds, unsubstituted or Rc-substituted C6-C 30 Arylene, unsubstituted or Rc-substituted C5-C 30 heteroaryl; The heteroatoms on the heteroaryl or heteroarylene group are each independently selected from O, S or N; The substituents Rc of each group are each independently selected from hydrogen, deuterium, halogen, nitro, cyano, C1-C4 alkyl, phenyl, biphenyl, terphenyl, pyridyl, pyrimidyl or naphthyl.
2. The organic electroluminescent device according to claim 1, characterized in that: R 1 and R 2 Each independently selected from hydrogen, C6-C 18 Aryl, unsubstituted or Rc-substituted C3-C 18 heteroaryl; and / or, Ar 1 Selected from C3-C containing N atom which is unsubstituted or substituted by Rc 18 heteroaryl; and / or, L 1 , L 2 Selected from chemical bonds, unsubstituted or Rc-substituted C6-C 18 Arylene, unsubstituted or substituted with Rc C5-C 30 Heteroaryl.
3. The organic electroluminescent device according to claim 1, characterized in that: The charge generation layer material includes Li or Yb, and the content of Li or Yb is 0.5%-2.5% of the charge generation layer material by mass percentage.
4. The organic electroluminescent device according to claim 1, characterized in that: The charge generation layer has a thickness of 10 nm to 30 nm.
5. The organic electroluminescent device according to claim 1, characterized in that: The compound of formula (I) is selected from the following compounds A1 to A30:
6. A display device, characterized in that: An organic electroluminescent device comprising any one of claims 1 to 5.
